THE DEVELOPMENT OF IMPEDANCE MATCHING NETWORK FOR WIRELESS POWER TRANSFER (WPT) SYSTEM - ABD RAHMAN, AMIRUL RIDHUAN (IRC, 2019)
Wireless power transfer system (WPT) is a system that that can transfer electricity without using any type of conductor. It means the electricity will be transferred wirelessly. The problem with the WPT system is when the distance between the two coils of the WPT is vary, it will also affect the efficiency of the system. The efficiency will keep dropping when the distance between the two coils of WPT are increasing. In this paper, the development of impedance matching network is proposed to install inside the WPT system. Impedance matching network can help to increase the efficiency of the WPT although the distance between two coils of WPT are increasing. Unfortunately, a convectional of impedance matching network design that commonly used not really give huge impact in improving efficiency of WPT system. So, another type of impedance matching network design will be proposed in this paper. The efficiency of the new design will be compared to a convectional impedance matching network that is commonly use for the WPT system.